Bed partner perception of CPAP therapy on relationship satisfaction and intimacy-A European perspective from the ESADA network - Laharnar, Naima; Bailly, Sebastien; Basoglu, Ozen K; Buskova, Jitka; Drummond, Marta; Fanfulla, Francesco; Mihaicuta, Stefan; Pataka, Athanasia; Riha, Renata L; Bouloukaki, Izolde; Testelmans, Dries; Trakada, Georgia; et al. (Journal of sleep research, 2024)
Obstructive sleep apnea increases morbidity and mortality risks. The most common treatment is continuous positive airway pressure, with nasal mask usage being important, but not always optimal. While most research on treatment adherence focuses on the patient, the bed partner's involvement may be detrimental. Our study aim is to obtain a European-wide picture of the bed partner's attitude and support towards continuous positive airway pressure therapy, including effects on relationship satisfaction and intimacy. The English translation of a German bed partner questionnaire, assessing relationship satisfaction and three major components (general attitude, perceived mask looks, intimacy effects) was distributed within the European Sleep Apnea Database Network and translated in participating countries' local language. Data were collected for 2 years. In total, 10 European countries (13 sleep centres) participated with 1546 questionnaires. Overall, 91% of bed partners had a positive attitude towards continuous positive airway pressure therapy, 86% perceived mask looks not negative, 64% stated no negative intimacy effects. More specifically, 71% mentioned improved sleep quality, 68% supported nightly device usage. For 41% of bed partners, relationship satisfaction increased (no change for 47%). These results were significantly more pronounced in Eastern/Southern Europe compared with Middle Europe, especially regarding intimacy effects. However, increased continuous positive airway pressure therapy length affected attitude negatively. These results provide necessary information to improve treatment strategies by including educational couple-focused approaches. Among others, we revealed that negative intimacy effects are not considered a barrier to continuous positive airway pressure adherence. These results may inspire more research identifying regional gaps with need for treatment adjustments.
Keywords: dospělí; průzkumy a dotazníky; Europe; Female; obstrukční spánková apnoe; osobní uspokojení; Adult; Perception; ženské pohlaví; Surveys and Questionnaires; Sexual Partners; sleep apnea; sexuální partneři; interpersonální vztahy; percepce; lidé; Personal Satisfaction; Evropa; questionnaire; continuous positive airway pressure therapy; relationship; Continuous Positive Airway Pressure; partner support; intimacy; Male; Sleep Apnea, Obstructive; Aged; trvalý přetlak v dýchacích cestách; lidé středního věku; Interpersonal Relations; senioři; mužské pohlaví; Middle Aged; Humans